956. COFFEA PERRIERI: Rubiaceae. (5th November 2020) - Davis, Aaron; Rakotonasolo, Franck
Summary: Coffea perrieri, one of 59 species of Coffea endemic to Madagascar is illustrated and described. It is compared with the commercial coffees, Arabica and robusta, and its habitat preferences, conservation risk, uses, and present distribution are discussed.